Is a History of Severe Episodic Low Back Pain an Indicator of a Discogenic Etiology?. Issue 7 (17th June 2017) - Levi, David; Carnahan, Diana; Horn, Scott; Levin, Josh
Abstract: Objective: To determine if a history of severe episodic low back pain (LBP) correlates with positive discography. Methods: A retrospective chart review identified patients undergoing discography from January 2012 through February 2016. The review determined if the patient's LBP began or continued with severe disabling episodes (lasting a minimum of two days). A gradual onset or initiating event with continuous symptoms was considered a nonepisodic history. Patients were excluded for unclear record, workers' compensation, litigation, prior lumbar surgery, radiologic instability, or indeterminate discography. Results: Seventy-eight patients underwent discography. Thirty-nine patients were included, 31 of which had positive discograms. Eight had negative discograms. Nineteen patients had a history of episodic LBP, and 20 had no history of episodic LBP. Of those 19 with a history of episodic LBP, 18 had positive discography and one had negative discography. Of those with no history of episodic LBP, 13 had positive discography and seven had negative discography. Using the historical finding of severe episodic LBP as a test for discogenic source of LBP, the sensitivity is 58% (95% confidence interval [CI] = 41–75%) and the specificity is 88% (95% CI = 65–100%). The likelihood ratio is 4.7 (95% CI = 0.72–30). The positive predictive value (PPV) is 95% (95% CI = 72–100%). The PPV is based upon a prevalence of 79% (discogram positive) in our sample of patients considering fusion surgery. The diagnostic confidence odds are 18.2, with a diagnostic confidence of 95%. Conclusions: A positive history of severe episodic LBP may be a strong indicator for a discogenic etiology.